Comparison of Ultrafast Papanicolaou Stain with the Standard Papanicolaou Stain in Body Fluids and Fine Needle Aspiration Specimens - Alwahaibi, Nasar Yousuf; Alsubhi, Mariam Said; Aldairi, Najat; Alshukaili, Amna; Bai, Usha Rani (Journal of Laboratory Physicians, 2016)
Introduction: Most cytology laboratories in all Gulf countries including Oman, use the standard papanicolaou (PAP) method to stain various cytological specimens. The aim of this study was to investigate the possible application of ultrafast PAP (UF‑PAP) method in cytology laboratory.Materials and Methods: Samples from 46 patients containing 26 body fluids and 20 fine needle aspirations (FNAs) (9 thyroids and 11 breasts) were collected. Two air dried and two wet smears from each sample were prepared and stained by UF‑PAP and the standard PAP stains, respectively. Background, nuclear staining, cell morphology, and overall staining were independently reviewed by two cytoscreeners.Results: In all cases of FNA, UF-PAP stain gave a good score for the background, nuclear staining, cell morphology, and overall staining when compared with the standard PAP method. Although the correct diagnosis was made in all cases of body cavity fluids cases except in one case, UF-PAP stain gave a fewer score in the assessment of body cavity fluid samples.Conclusion: The findings of this study support the use of UF‑PAP method in cytology laboratory with a high emphasis on FNA samples.
Keywords: Body cavity fluids; cytology; fine needle aspiration; papanicolaou; ultrafast papanicolaou